AM1*parameters for aluminum, silicon, titanium and zirconium - Winget, Paul; Clark, Timothy (Journal of Molecular Modeling, 2005)
Our extension of the AM1 semiempirical molecular orbital technique, AM1*, has been parameterized for the elements Al, Si, Ti and Zr. The basis sets for all four metals contain a set of d-orbitals. Thus, AM1* parameters are now available for H, C, N, O and F (which use the original AM1 parameters), Al, Si, P, S, Cl, Ti, Mo and Zr. Special attention was paid to reproducing homolytic and heterolytic bond-dissociation energies correctly. Such bond-energy data help to avoid eccentricities in the parameterization caused by inaccurate experimental heats of formation. The performance and typical errors of AM1* for the newly parameterized elements are discussed. Generally, the new method performs less well than established techniques for heats of formation but considerably better for the heats of reaction.
Keywords: AM1*; parameterization; aluminum; silicon; titanium; zirconium; semiempirical MO-theory